Makna Nyanyian Syukur dalam Lagu-Lagu Regio Kalimantan Hasil Lokakarya Tering 1985 - Samuel Wua Hului; Wilfridus Samdirgawijaya; Gervasius Panggur Masuri (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
This paper briefly describes the results of the study on the comprehension of the Parishioners at the Parish of Keluarga Suci, Tering about the meaning of the Hymns of Thanks: “Berkatilah Ya Tuhan” and “Berkat Tuhan Kami Harap” introduced after the Liturgical Music Workshop conducted at Tering in 1985. The Parishioners’ comprehension about the meaning of the two Hymns, qualitatively belonged to the category of Relational Comprehension. The Parishioners apprehended the two Hymns in the realm of both their Faith Meaning category and their Contextual Meaning category, interrelatedly and integrated. The interconnection between the two meaning categories lies in their Gratitude Meaning in both local people’s Custom and in Church Liturgy. The Faith Meaning is achieved through the Gratitude Meaning in their Church Devotion / Liturgy, and the Contextual Meaning is achieved through the Gratitude Meaning in their local Custom. The Gratitude Meaning in local people’s Custom is apparently very similar to the Gratitude Meaning in Catholic Faith. Faith Meaning was visible from the Parishioners’ comprehension, elucidated the Hymns of Thanks as Faith Meaning, expressing both spiritual participation and physical participation in the forms of gratitude, thanks, hope, request and strength from God’s mercy, by faith in the Holy Trinity. Contextual Meaning on the other hand was visible from the Parishioners’ comprehension, elucidated the Hymns of Thanks in their Contextual Meaning, expressing spiritual and physical participation in a new manner by transforming the local Custom context to the Catholic Church Devotion context. So it can be said that for the Parishioners the Gratitude Meaning in their Catholic Faith is inseparable from the Gratitude Meaning in their local Custom, and on the other way around the Gratitude Meaning in their local Custom is inseparable from the Gratitude Meaning in their Catholic Faith. In such way the Hymns of Thanks: “Berkatilah Ya Tuhan” and “Berkat Tuhan Kami Harap” relate the Contextual Meaning in local Custom and the Faith Meaning of the Hymns in Catholic Church Liturgical Devotion.